School Strategy in Shaping the Character of Grade IV Students at Sandika Elementary School - Insantuan, Balthasar; Sihotang, Hotmaulina (CV. Publikasi Indonesia, 2025)
Strategies for improving student character refer to plans and methods designed to develop and strengthen positive traits in students. This research aims to explore and analyze the strategies implemented by Sandika Elementary School in shaping the character of class IV students. Using qualitative research methods, data was collected through in-depth interviews with 6 teachers as participants, using classroom observation techniques, and document analysis related to the character education program. The research results show that the strategies implemented include the integration of character values in the curriculum, the use of active learning methods, and the involvement of parents and the community in the education process. Apart from that, creating a positive and safe school environment is also a main focus. The results of this study indicate that the character education strategies implemented at Sandika Elementary School have produced observable and meaningful changes in student behavior, especially among class IV students. Through the integration of character values such as discipline, responsibility, honesty, and respect into daily learning activities, students demonstrated increased consistency in applying these values both in the classroom and in their interactions outside of school. For instance, teachers noted a decrease in disciplinary issues and an increase in student participation, cooperation, and empathy during group work. Students also began to display more initiative in maintaining cleanliness, arriving on time, and helping peers without being instructed. Parental testimonies further supported these observations, noting improved attitudes at home, including better communication, independence, and respect toward family members.